2007
DOI: 10.1113/jphysiol.2007.130013
|View full text |Cite
|
Sign up to set email alerts
|

Potassium initiates vasodilatation induced by a single skeletal muscle contraction in hamster cremaster muscle

Abstract: The rapid onset of vasodilatation within seconds of a single contraction suggests that the vasodilators involved may be products of skeletal muscle activation, such as potassium (K + ). To test the hypothesis that K + was in part responsible for the rapid dilatation produced by muscle contraction we stimulated four to five skeletal muscle fibres in the anaesthetized hamster cremaster preparation in situ and measured the change in diameter of arterioles at a site of overlap with the stimulated muscle fibres bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
101
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 79 publications
3
101
1
Order By: Relevance
“…Based on different experimental models, such latency is currently reported to be "Ͻ1 s" (24,33,41,47), which is considered too short for the metabolic action to develop (11,50). However, a recent study indicates that K ϩ , released by con-tracting muscle fibers, could also mediate an early dilatory effect (2), which leaves the issue unsettled. Based on the similarity in the rapid hyperemic responses that have been reported in different preparations in response to short-lasting muscle contractions and mechanical stimuli (6,8,10,18,24,33,38,47), we hypothesized that a single mechanosensitive mechanism, activated by changes in transmural pressure, could underlie the different responses.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Based on different experimental models, such latency is currently reported to be "Ͻ1 s" (24,33,41,47), which is considered too short for the metabolic action to develop (11,50). However, a recent study indicates that K ϩ , released by con-tracting muscle fibers, could also mediate an early dilatory effect (2), which leaves the issue unsettled. Based on the similarity in the rapid hyperemic responses that have been reported in different preparations in response to short-lasting muscle contractions and mechanical stimuli (6,8,10,18,24,33,38,47), we hypothesized that a single mechanosensitive mechanism, activated by changes in transmural pressure, could underlie the different responses.…”
mentioning
confidence: 90%
“…By administering different dilatory metabolites to isolated skeletal muscle arterioles it was shown that at least 4 s are required to elicit dilatation (50). More recently Armstrong et al (2) suggested that potassium released by the excitation of muscle fibers could play a major role in the early dilatory process, based on the observation that the dilatation (evaluated at 4 s after muscle contraction) was markedly reduced by application of various blockers of the K ϩ signaling pathway. However, these data have been questioned (9,23) on the basis of the following two facts: 1) some of the pharmacological interventions weakened the contraction of skeletal muscle fibers, thus also attenuating the mechanical action exerted on blood vessels; and 2) voltagegated K ϩ channels are also implicated in the myogenic response (15), and thus their blockade might have impaired the myogenic reactivity of the vascular network.…”
Section: The Rapid Hyperemic Response To Brief Spontaneous Contractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, experiments measuring blood flow to the canine hindlimbs (14,15) indicate that vasodilation is necessary for the immediate hyperemia at the onset of muscle contraction. Studies published over the last decade have provided evidence for the involvement of adenosine (2), potassium (8,9), and vascular compression (6,16,37) in rapid vasodilation of the skeletal muscle resistance vasculature.…”
mentioning
confidence: 99%
“…Experiments performed using the hamster cremaster (2,24) or retractor muscles (39) demonstrate that muscle contraction causes vasodilation of arterioles within 2-3 s of the onset of muscle contraction. Experiments performed in the human forearm (34,36) and dog hindlimb (26) indicate that the muscle pump cannot explain the entire hyperemic response to muscle contraction.…”
mentioning
confidence: 99%